1995
DOI: 10.2307/4002802
|View full text |Cite
|
Sign up to set email alerts
|

Spotted Knapweed Seed Viability after Passing through Sheep and Mule Deer

Abstract: Spotted knapweed (Centaureu maculosa Lam.), an introduced perennial plant, has invaded large areas of rangeland in the northwestern United States. Grazing animals may disseminate the weed by transporting seeds in their digestive system and depositing them in their feces. In this study percent viability and emergence of spotted hnapweed seeds that passed through mule deer (Odocoileus hemionus hemionus) and sheep (Ovis aries) were determined. Percent viability included seeds that germinated and seeds that tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Invasive plant seeds have been recovered from feces and found viable in numerous studies (Thill et al, 1986;Wallander et al, 1995;Malo et al, 2000;Olson and Wallander, 2002). Malo et al (2000) concluded that the effect of seed input to the seed bank from ungulate transport may be low at large and medium-sized spatial scales, but very important at small scales and for colonization processes.…”
Section: Endozoochory and Epizoochorymentioning
confidence: 99%
“…Invasive plant seeds have been recovered from feces and found viable in numerous studies (Thill et al, 1986;Wallander et al, 1995;Malo et al, 2000;Olson and Wallander, 2002). Malo et al (2000) concluded that the effect of seed input to the seed bank from ungulate transport may be low at large and medium-sized spatial scales, but very important at small scales and for colonization processes.…”
Section: Endozoochory and Epizoochorymentioning
confidence: 99%
“…In the past, numerous plant species were introduced to Europe via sheep fleeces (Ridley 1930 Sheep consuming leafy spurge seeds may also disperse viable seeds in their feces (Harmon and Keim 1934, Lehrer and Tisdale 1956, Özer 1979, Thill et al 1986, Simao Neto et al 1987, Dastgheib 1989. Viability of seed recovered from feces may be enhanced or reduced compared with seed that has not passed through sheep (Harmon and Keim 1934, Lacey et al 1992, Wallander et al 1995. Germinability of seeds recovered from feces generally decreases as residence time in the gastrointestinal tract of sheep increases (Özer 1979, Lacey et al 1992, Wallander et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Viability of seed recovered from feces may be enhanced or reduced compared with seed that has not passed through sheep (Harmon and Keim 1934, Lacey et al 1992, Wallander et al 1995. Germinability of seeds recovered from feces generally decreases as residence time in the gastrointestinal tract of sheep increases (Özer 1979, Lacey et al 1992, Wallander et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly surprising because native and introduce ungulates dominate most western US landscapes. Viable seeds of invasive plants have been recovered from dung in several studies, but data are limited to a small handful of species including leafy spurge (Euphorbia esula), common crupina (Crupina vulgaris), spotted knapweed (Centaurea maculosa), and Lehmann lovegrass (Eragrostis lehmanniana) (Fredrickson et al, 1997;Olson et al, 1997;Wallander et al, 1995).…”
Section: Article In Pressmentioning
confidence: 99%